Stigmatization of Chinese and Asian-looking people during the COVID-19 pandemic in Germany - Julia E. Koller; Karoline Villinger; Nadine C. Lages; Isabel Brünecke; Joke M. Debbeler; Kai D. Engel; Sofia Grieble; Peer C. Homann; Robin Kaufmann; Kim M. Koppe; Hannah Oppenheimer; Vanessa C. Radtke; et al. (BMC, 2021)
Abstract Background The outbreak and global spread of COVID-19 was accompanied by an increase in reports of stigmatization of Chinese and Asian-looking people. The behavioral immune system provides a framework for stigmatization in response to infectious disease threats. Specifically, stigmatization might increase with rising levels of infectious disease threat. The present study aimed to examine this hypothesis during the early phase of the COVID-19 pandemic. Methods As part of the "EUCLID" project ( https://euclid.dbvis.de ), a total of 5011 persons from Germany were surveyed via an online-questionnaire between February 2nd and April 3rd, 2020, covering the progression of the COVID-19 pandemic over three time periods which were defined by critical events. Results There was no evidence for an increase in the stigmatization of Chinese and Asian-looking people across three topics, that is personal proximity, air travel, and medical measures upon arrival from China. Conclusions The present findings provide good news in that participants showed an adaptive response to the infectious disease threat rather than displaying increased stigmatization. Further research is necessary to specify the conditions that increase the risk of stigmatization in response to infectious disease threats.